Biographical Approach: Two Theoretical-Methodological Strands - Kraniauskienė, Sigita (Sociologija. Mintis ir veiksmas, 2000)
The aim of the article is to discuss the theoretical and methodological bases of the biographical approach in sociology. Such a discussion is developed through a comparative analysis of two strands of the biographical approach: the „generalizing“ strand that is built on a positivistic methodology on the one hand and the „individualizing“ strand that is built upon the ideas of sociology of knowledge, phenomenological sociology and hermeneutics on the other. In developing her analysis the author attempts to consider the possibilities of the biographical approach to mediate the quantitative and qualitative divide in sociology.
Keywords: biographical method; generalizing tradition; individualizing tradition; qualitative methodology